Some Aspects of Resistance against Forced Collectivization in the Region of Nový Bydžov (Theatrum historiae, 2012)
The rural resistance to subjugation in the form of violent collectivization is the main theme of the contribution. Through a micro-historic view of the sixty-year-old events, which took place in the then Nový Bydžov district, the author tries to highlight the vitality and variety of the forms of resistance to the establishment of unified agricultural cooperatives and thus to contribute to the discussion on anti-communist resistance and opposition. The author also puts forward a detailed analysis of the State Security (StB) provocation action, for which the setting up of informers among anti-communist leaning members of the population became a primary task. It also tries to answer the question of what role the StB and its methods played in the collectivization process.
Keywords: Nový Bydžov district; countryside; collectivization; resistance; StB provocation